Circular economy: Transforming solid-wastes to useful products - Rana, Supriyanka; Mishra, Puranjan; Gupta, Reena; Zularisam, A. W.; Singh, Lakhveer (Elsevier, 2020)
Present 21st century world has started facing several challenges (such as waste management, bioresource scarcity, food/and energy security, climate change, global warming and health risks) as a heavy price of reckless usage/or exploitation of natural resource. In such a scenario, the implementation of circular economy model (based on use, produce, consume, waste recovery/or recycling, sharing, leasing, reusing, repairing, renovating, refurbishing and using waste feedstock to produce secondary products) emerged as the best sustainable option than linear economy model (based on use, produce, consume and waste discard). Inculcation of circularity in every aspect of our life (behavior, livelihood, economy, infrastructure) can help us in attaining long-term goals of sustainability and harmonizing human existence on planet Earth. Recent technological advancements have assisted in creating sustainable methods (incineration, pyrolysis, composting, anaerobic digestion) for treating or recycling the enormous solid waste, thereby enhancing valuable product recovery (such as heavy metals, biogases, bioelectricity, feedstock). So, it is necessary to develop more efficient sustainable waste-to-energy technologies capable of reutilizing solid wastes and helping to safeguard the environment from waste generated hazards. This chapter deals with sustainable ways to incorporate solid wastes into the circular loop of circular economy model. This chapter will present practical solutions for solid waste recycling and for fully realizing the potential of solid waste in circular economy in terms of more revenues.